Interorganizational triads for foreign-market entry: Partnerships among Western, bridge-economy, and local VCs in mainland China - Zhang, Jing; Zhang, Wei; Schwab, Andreas (Journal of business venturing, 2024)
This study introduces the novel construct of bridge-economy partners, which can assist Western firms in learning how to collaborate with local partners when entering unfamiliar foreign countries that have substantially different socioeconomic characteristics. We offer initial empirical evidence regarding the relevance of establishing such interorganizational partnership triads among Western, bridge-economy, and local firms for the entries of Western venture capital firms (VCs) into Mainland China between 1997 and 2008. Venture age, regional legal maturity, and the Western VCs' accumulated local experience are identified as relevant contingency factors for the likelihood of adopting this type of collaboration, which involves partners from three different types of economies. We supplement our quantitative analyses with anecdotal qualitative evidence from interviews with VC executives and fund managers. This study introduces the novel construct of bridge-economy partners and outlines their potentially beneficial roles in the context of foreign-market entry undertaken by Western firms. The established literature suggests that Western firms consider collaboration with a local firm as an accelerator for learning about and adapting to local conditions. However, the substantial socioeconomic differences that may exist between home and host country can create paramount challenges for collaborations between Western firms and their local partners. Adding a third type of partner from a country with substantial socioeconomic overlap to both firms' home countries can help “bridge the socioeconomic gap” between Western and local firms. The bridge-economy partners can assist Western firms in learning how to collaborate with their new local partners. This study offers initial empirical evidence for the relevance of such interorganizational partnership triads between Western, bridge-economy, and local firms by using the data of Western venture capital firms (VCs) and their entries into Mainland China between 1997 and 2008. Venture age, regional legal maturity, and accumulated local experience of Western VCs are identified as relevant contingency factors for the likelihood of adopting this type of triadic interorganizational partnership. Quantitative hypothesis tests are supplemented with anecdotal qualitative evidence. Reported findings extend the emerging entrepreneurship literature that focuses on foreign-market entry and globalization. Our focus on triadic partnerships and the role of bridge-economy firms extends the previous research that has instead nearly exclusively focused on dyadic collaborations between Western firms and local partners. A triadic WBL partnership offers an alternative strategy to use when entering foreign markets that have substantially different cultural, economic, and institutional characteristics. Our findings further highlight that even though such triadic WBL partnerships make intuitive sense, successfully implementing such complex collaborations requires minimum levels of accumulated host-country experiences and can benefit from mature legal environments. For policymakers in emerging economies that are interested in supporting foreign investment, the creation of legal environments conducive to forming such triadic WBL collaborations introduces a promising policy option. Beyond these initial key insights, this study also provides guidance for systematic future research into this promising type of collaboration for foreign market entry. •Partners from bridge-economies can help foreign firms collaborate with locals entering extremely different countries.•Western VCs are more likely to form the triadic partnership when investing in younger ventures.•Western VCs are more likely to form the triadic partnership when investing in regions with more mature legal systems.•There is a J-shaped relationship between Western VC local experience and propensity to form the triadic partnership.